Nigeria trade and investment directory : A-Z of business in Nigeria - Federal Ministry of Trade and Investment (Abuja : Federal Ministry of Trade and Investment, 2013)
A compendium of investment opportunities in Nigeria with incisive and indepth analysis of each sector of the national economy.
Issued by: Federal Ministry of Trade and Investment <2013/14->
oif 25/02/2015
Ref.
Keywords: Investments; Foreign Trade; Corporations; Industries; Nigeria